An empirical analysis of a regional Dutch disease: the case of Canada - Papyrakis, E; Raveh, O (University of Oxford, 2013)
While there has been extensive research on the Dutch Disease (DD), very little attention, if any, has been devoted to the regional mechanisms through which it may manifest itself. This is the first empirical attempt to research a 'regional DD' by looking at the local and spatial impacts of resource windfalls across Canadian provinces and territories. We construct a new panel dataset to examine separately the key DD channels; namely, the Spending Effect (SE) and the Resource Movement Effect (RME). Our analysis reveals that the standard DD mechanisms are also relevant at the regional level; specifically, we find that: (a) Resource windfalls are associated with higher inflation and a labour (capital) shift from (to) non-primary tradable sectors. (b) Resource windfalls in neighbouring regions are associated with a capital (labour) shift from (to) non-primary tradable sectors in the source region. (c) The (spatial) DD explains (51%) 20% of the adverse effects of resource windfalls (in neighbouring regions) on region-specific non-mineral international exports (in the source region), and does not significantly affect domestic ones.